Association between Admission Hyperglycemia and Culprit Lesion Characteristics in Nondiabetic Patients with Acute Myocardial Infarction: An Intravascular Optical Coherence Tomography Study - Jinying Zhou; Zhaoxue Sheng; Chen Liu; Peng Zhou; Jiannan Li; Runzhen Chen; Li Song; Hanjun Zhao; Hongbing Yan (Journal of Diabetes Research)
Background. Hyperglycemia is frequently observed in acute myocardial infarction (AMI). Diabetes mellitus (DM) patients and non-DM patients have different culprit lesion phenotypes and few data are available on non-DM patients with admission hyperglycemia. Therefore, we aimed to investigate the association between admission hyperglycemia and culprit lesion characteristics using optical coherence tomography (OCT) in AMI patients. Methods and Results. We consecutively enrolled 434 patients with AMI, and 277 patients were included in analysis: 65.7% (n=182) non-DM patients and 34.3% (n=95) DM patients. We measured acute blood glucose (ABG) and hemoglobin A1c to calculate the acute-to-chronic glycemic ratio (A/C). Then, we grouped non-DM patients into tertiles of A/C. OCT-based culprit lesion characteristics were compared across A/C tertiles in non-DM patients and between DM and non-DM patients. Non-DM patients had fewer lipid-rich plaques (52.7% versus 68.4%, p=0.012) and thin-cap fibroatheroma (TCFA) (19.8% versus 34.7%, p=0.006) than DM patients but similar prevalence of plaque rupture (47.3% versus 56.8%, p=0.130). Non-DM patients with the highest A/C tertile had the highest prevalence of plaque rupture (pfor trend=0.002), lipid-rich plaque (pfor trend=0.001), and TCFA (pfor trend=0.003). A/C>1.22 but not ABG>140 mg/dl predicted a high prevalence of plaque rupture, lipid-rich plaque, and TCFA in non-DM patients. Conclusions. In AMI patients without DM, admission hyperglycemia is associated with vulnerable culprit lesion characteristics, and A/C is a better predictor for vulnerable culprit plaque characteristics than ABG. These results call for a tailored evaluation and management of glucose metabolism in nondiabetic AMI patients. This trial is registered with NCT03593928.